The born-again (very late thermal pulse) scenario revisited: The mass of the remnants and implications for V4334 Sgr - Miller Bertolami, Marcelo Miguel (2007)
We present 1D numerical simulations of the very late thermal pulse (VLTP) scenario for a wide range of remnant masses. We show that by taking into account the different possible remnant masses, the observed evolution of V4334 Sgr (a.k.a. Sakurai's object) can be reproduced within the standard 1D mixing length theory (MLT) stellar evolutionary models without the inclusion of any ad hoc reduced mixing efficiency. Our simulations hint at a consistent picture with present observations of V4334 Sgr. From energetics, and within the standard MLT approach, we show that low-mass remnants (M ≲ 0.6 M⊙) are expected to behave markedly differently from higher mass remnants (M ≳ 0.6 M⊙) in the sense that the latter remnants are not expected to expand significantly as a result of the violent H-burning that takes place during the VLTP. We also assess the discrepancy in the born-again times obtained by different authors by comparing the energy that can be liberated by H-burning during the VLTP event.